Contrast‐Enhanced Ultrasound Differentiation Between Low‐ and High‐ Grade Bladder Urothelial Carcinoma and Correlation With Tumor Microvessel Density. (27th May 2017) - Guo, Suping; Xu, Pan; Zhou, Aiyun; Wang, Gongxian; Chen, Weimin; Mei, Jinhong; Xiao, Fan; Liu, Juan; Zhang, Cheng
Abstract : Objectives: Time‐intensity curves (TICs) of contrast‐enhanced ultrasound (CEUS) were analyzed retrospectively to differentiate between low‐grade and high‐grade bladder urothelial carcinoma, and to investigate correlation with tumor microvessel density (MVD). Methods: The data of 105 patients with pathologically confirmed bladder urothelial carcinoma (55 low‐grade and 50 high‐grade) were reviewed. Lesions were examined before surgery using conventional ultrasound and CEUS with TIC analysis. The TIC parameters time from peak to one‐half the signal intensity (TPH) and the corresponding descending slope (DS) of the low‐grade and high‐grade groups were compared, and receiver operating characteristic curves constructed. The MVDs of the resectioned tissue specimens were quantified via immunohistochemistry for CD34. Results: Based on conventional ultrasound, the low‐grade and high‐grade groups were similar in tumor shape, number, topography, internal echo, height, width, and vascularity. The TPH of the high‐grade group was significantly longer than that of the low‐grade group, and the DS was lower. The cutoff points of TPH and DS for differentiating low‐grade and high‐grade bladder urothelial carcinoma were 48.06 seconds and 0.15 dB/seconds, respectively (area under the receiver operating characteristic curve = 0.79 for both). The mean MVDs per high‐power field of the low‐grade and high‐grade groups were 41.39 16.65 and 51.03 20.16, respectively ( P = .009). The TPH correlated linearly with MVD ( P < .01), as did the DS ( P < .01). Conclusions: Contrast‐enhanced ultrasound can be used to differentiate low from high‐grade bladder urothelial carcinoma. The TIC parameters of CEUS reflect the MVD of bladder urothelial tumors and may be helpful for evaluating tumor angiogenesis, with implications for clinical diagnosis, treatment, and prognosis.